On the Solvability of a System of Linear Equations Over the Domain Of Principal Ideals - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We propose new necessary and sufficient conditions for the solvability of a system of linear equations over the domain of principal ideals and an algorithm for the solution of this system.